Time to stroke: A Western Trauma Association multicenter study of blunt cerebrovascular injuries. Issue 5 (November 2018) - Burlew, Clay Cothren; Sumislawski, Joshua J.; Behnfield, Charles D.; McNutt, Michelle K.; McCarthy, James; Sharpe, John P.; Croce, Martin A.; Bala, Miklosh; Kashuk, Jeffry; Spalding, M. Chance; Beery, Paul R.; John, Scott; et al.
Abstract : BACKGROUND: Screening for blunt cerebrovascular injuries (BCVIs) in asymptomatic high-risk patients has become routine. To date, the length of this asymptomatic period has not been defined. Determining the time to stroke could impact therapy including earlier initiation of antithrombotics in multiply injured patients. The purpose of this study was to determine the time to stroke in patients with a BCVI-related stroke. We hypothesized that the majority of patients suffer stroke between 24 hours and 72 hours after injury. METHODS: Patients with a BCVI-related stroke from January 2007 to January 2017 from 37 trauma centers were reviewed. RESULTS: During the 10-year study, 492 patients had a BCVI-related stroke; the majority were men (61%), with a median age of 39 years and ISS of 29. Stroke was present at admission in 182 patients (37%) and occurred during an Interventional Radiology procedure in six patients. In the remaining 304 patients, stroke was identified a median of 48 hours after admission: 53 hours in the 144 patients identified by neurologic symptoms and 42 hours in the 160 patients without a neurologic examination and an incidental stroke identified on imaging. Of those patients with neurologic symptoms, 88 (61%) had a stroke within 72 hours, whereas 56 had a stroke after 72 hours; there was a sequential decline in stroke occurrence over the first week. Of the 304 patients who had a stroke after admission, 64 patients (22%) were being treated with antithrombotics when the stroke occurred. CONCLUSIONS: The majority of patients suffer BCVI-related stroke in the first 72 hours after injury. Time to stroke can help inform clinicians about initiation of treatment in the multiply injured patient. LEVEL OF EVIDENCE: Prognostic/Epidemiologic, level III.